2021
DOI: 10.1177/03635465211018216
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparison of Latissimus Dorsi Transfer and Pectoralis Major Transfer for Irreparable Subscapularis Tendon Tear: A Systematic Review

Abstract: Background: Latissimus dorsi transfer (LDT) and pectoralis major transfer (PMT) were developed to treat an irreparable subscapularis tendon tear (ISScT); however, the difference in their outcomes remains unclear. Purpose: To systematically review and compare the outcomes of LDT and PMT for ISScT. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review was performed through a comprehensive search of Embase, PubMed, and the Cochrane Library. Studies of LDT or PMT were included accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 87 publications
3
26
0
1
Order By: Relevance
“…However, when each are expressed as a percentage of the best possible score, Constant–Murley scores are 63% and 69% in the PMT and LDT groups, respectively, whereas the mean ASES score in our cohort is 89%. 24 Luo et al. 24 reported failure rates of 12.9% for PMT and 7.1% for LDT which is comparable to our failure rate of 14.3% (1 patient).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, when each are expressed as a percentage of the best possible score, Constant–Murley scores are 63% and 69% in the PMT and LDT groups, respectively, whereas the mean ASES score in our cohort is 89%. 24 Luo et al. 24 reported failure rates of 12.9% for PMT and 7.1% for LDT which is comparable to our failure rate of 14.3% (1 patient).…”
Section: Discussionsupporting
confidence: 82%
“… 8 , 10 In a recent systematic review, Luo et al. 24 reviewed 9 PMT and 3 LDT studies reporting average postoperative Subjective Shoulder Value scores of 71 for PMT and 70 for LDT. These values are comparable to our cohort’s average SANE score of 71, an outcome measure analogous to the Subjective Shoulder Value.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the abundance of non‐randomized studies in the included literature, two reviewers (JY and ZX) critically appraised (independently) all eligible studies against the Methodological Index for Nonrandomized Studies (MINORS) to assess their quality. 32 , 33 A senior reviewer (ZL) made the final assessment decision when consensus could not be achieved. The MINORS instrument contains 12 items (Supporting Information S3 ): eight for noncomparative studies with an additional four for comparative studies.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, Grades 4A, 4B, and 5 were grouped together as Grade 4-5 because these grades are characterized by glenohumeral arthritis with massive RCT, which is often used as an exclusion criterion for joint-preserving surgery and a good indication for reverse shoulder arthroplasty. 3 , 10 , 24
Figure 1 Classification of Hamada Grade. ( A ) Grade 1, the acromiohumeral interval is 6 mm or more.
…”
Section: Methodsmentioning
confidence: 99%
“… 14 , 15 Recently, preoperative radiographic evaluation according to the Hamada classification has been widely used to determine the indication for joint-preserving surgery in patients with symptomatic RCTs. 5 , 8 , 15 , 19 , 24 , 26 , 39 In addition, some studies have reported that progressed Hamada Grades worsen the clinical results of rotator cuff surgery. 8 , 15 , 29 However, the correlation between the severity of the Hamada Grade and the underlying rotator cuff and long head of the biceps (LHB) pathologies remains unclear.…”
mentioning
confidence: 99%